Improved Distributed Predictive Functional Control With Basic Function and PID Control Structure - Zhe Yu; Jianjun Bai; Hongbo Zou (IEEE Access, 2020)
It is known that constraints and disturbances in practice may affect the performance of distributed predictive functional control (DPFC) system greatly, thus it is necessary to develop a method to enhance the control performance further. Based on such background, a modified predictive functional control with basic function and PID control structure (BFPID-DPFC) is proposed for large-scale strong coupling system in this paper. In this approach, the performance index is reconstructed by utilizing the Proportional integral derivative (PID) factor and the weighting coefficient of basis functions firstly, then the ensemble control performance of the strong coupling system can be improved by adjusting the corresponding factors. Further, the coupling effect between subsystems can be eliminated by employing Nash game theory, then the improved DPFC approach is obtained. The comparisons between conventional DPFC method and the BFPID-DPFC approach are done in the simulation part, and the results show that the ensemble control performance of the proposed DPFC algorithm is better.